From Husserl to Merleau-Ponty: Tracing the Arc of Phenomenology - Iqbal Hussain Alamyar (Program Studi Filsafat Universitas Katolik Widya Mandira Kupang, 2024)
This research traces the key developments in phenomenological thought from its inception with Edmund Husserl to its evolution under Maurice Merleau-Ponty. The primary objective is to understand the continuity and divergence in their perspectives, and the influence on phenomenology’s progression as a philosophical tradition. The study employs a conceptual and thematic analysis method to elucidate these developments by examining their foundational texts. The findings reveal a nuanced understanding of this evolution, highlighting both Husserl’s establishment of transcendental phenomenology focused on pure consciousness and Merleau-Ponty’s transformative turn toward embodied experience. By synthesizing connections between their projects, this analysis provides a comprehensive view of the arc of phenomenological thought. Keywords: Phenomenology, Husserl & Merleau-Ponty, Intentionality, Consciousness, Embodiment